Clinical manifestations and risk factors of immune-related thyroid adverse events in patients treated with PD-1 inhibitors: a case-control study - Zhao, Pengfei; Li, Jia; Yu, Lihong; Ma, Wenming; Zhao, Ting (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint inhibitors (ICPIs) have emerged as a powerful strategy to cancer treatment. However, while demonstrating antitumor efficacy, they can also induce a range of immune-related adverse events (irAEs). Immune-related thyroid dysfunction is one of the most common irAEs. This study aims to investigate the clinical characteristics and identify potential risk factors associated with PD-1 inhibitor-induced immune-related thyroid dysfunction in real-world.MethodsA retrospective analysis was conducted on the clinical data of cancer patients treated with PD-1 inhibitors at Weifang People’s Hospital from January 2021 to December 2024. The incidence, clinical subtypes, onset time, and prognostic outcomes of thyroid dysfunction were analyzed. Univariate and multivariate logistic regression analyses were performed to identify risk factors.Results119 patients of PD-1 inhibitor-associated thyroid dysfunction were identified. The overall incidence of thyroid dysfunction was 2.97%, with hypothyroidism occurring in 1.20%, hyperthyroidism in 1.77%, and thyroiditis in 0.50% of patients. Tislelizumab exhibited the highest incidence at 3.48%, followed by camrelizumab at 3.10%, sintilimab at 2.24%, and toripalimab at 1.75%. The median time from the initiation of immunotherapy to the onset of thyroid dysfunction was 67 days, with hypothyroidism and hyperthyroidism developing at median times of 64.5 and 69 days, respectively. 77.31% of cases occurred within the first four months of immunotherapy. Female gender, lower baseline FT3 levels, history of targeted therapy, and baseline TgAb positivity were identified as independent risk factors for PD-1 inhibitor-associated thyroid dysfunction. Furthermore, higher baseline TSH levels, younger age, and treatment with tislelizumab or camrelizumab were associated with an increased risk of immune-related hypothyroidism, whereas lower baseline TSH levels were linked to a higher risk of immune-related hyperthyroidism.ConclusionsClose clinical and hormonal monitoring is recommended for patients with high-risk factors before and throughout the course of immunotherapy, particularly during the initial 2 to 4 months of PD-1 inhibitor treatment.